Traffic noise affects forest bird species in a protected tropical forest - J. Edgardo Arévalo; Kimberly Newhard (Revista de Biología Tropical, 2011)
The construction of roads near protected forest areas alters ecosystem function by creating habitat fragmentation and through several direct and indirect negative effects such as increased pollution, animal mortality through collisions, disturbance caused by excessive noise and wind turbulence. Noise in particular may have strong negative effects on animal groups such as frogs and birds, that rely on sound for communication as it can negatively interfere with vocalizations used for territorial defense or courtship. Thus, birds are expected to be less abundant close to the road where noise levels are high. In this study, we examined the effects of road traffic noise levels on forest bird species in a protected tropical forest in Costa Rica. Data collection was conducted in a forest segment of the Carara National Park adjacent to the Coastal Highway. We carried out 120 ten minute bird surveys and measured road noise levels 192 times from the 19th to the 23rd of April and from the 21st to the 28th of November, 2008. To maximize bird detection for the species richness estimates we operated six 12m standard mist nets simultaneously with the surveys. The overall mist-netting effort was 240net/h. In addition, we estimated traffic volumes by tallying the number of vehicles passing by the edge of the park using 24 one hour counts throughout the study. We found that the relative abundance of birds and bird species richness decreased significantly with the increasing traffic noise in the dry and wet season. Noise decreased significantly and in a logarithmic way with distance from the road in both seasons. However, noise levels at any given distance were significantly higher in the dry compared to the wet season. Our results suggest that noise might be an important factor influencing road bird avoidance as measured by species richness and relative abundance. Since the protected forest in question is located in a national park subjected to tourist visitation, these results have conservation as well as management implications. A decrease in bird species richness and bird abundance due to intrusive road noise could negatively affect the use of trails by visitors. Alternatives for noise attenuation in the affected forest area include the enforcement of speed limits and the planting of live barriers. Rev. Biol. Trop. 59 (2): 969-980. Epub 2011 June 01. Las carreteras cerca de bosques alteran la función del ecosistema por fragmentación del hábitat y tienen otros efectos negativos como contaminación, mortalidad de animales y ruido excesivo; sobre todo en animales como ranas y aves que dependen del sonido para comunicarse. Se espera menos abundancia de aves cerca de la carretera donde el ruido es alto. Este estudio evalúa los efectos del ruido por carretera sobre las aves en un bosque tropical de Costa Rica. También realizamos censos de aves y medimos el ruido del 19 al 23 de abril y del 21 al 28 de noviembre 2008. Además, utilizamos redes de niebla para maximizar la detección de aves en la estimación de riqueza de especies. La abundancia de aves así como la riqueza de especies decrecieron significativamente con el incremento del ruido tanto en la estación seca como en la lluviosa. El ruido disminuyó en forma logarítmica con el aumento en la distancia a la carretera y fue más alto durante la estación seca. Nuestros resultados sugieren que las aves tienden generalmente a evitar el ruido del tráfico y tienen implicaciones en la conservación y manejo del área protegida